Healthy Living Behaviors: Application of the Project Based Learning Model in Grade IV Students of Physical Education Subjects - Sahbana Ridha; Mashud; Herita Warni; Syamsul Arifin (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Healthy living habits are critical for optimal quality of life, yet schools often fall short in instilling these practices effectively. This study investigates the impact of the Project-Based Learning (PjBL) model on enhancing healthy living behaviors among fourth-grade students in PJOK (Physical Education, Sports, and Health) classes. Utilizing Classroom Action Research, this study was conducted over two cycles, each with phases of planning, action, observation, and reflection, involving 27 students from SD Negeri 5 Sungai Ulin. The data were collected through student worksheets, interviews, observations, and performance tests, focusing on essential healthy habits: physical activity, balanced nutrition, rest, and productive use of free time. Findings indicate a substantial improvement, with 70% of students meeting criteria in cycle I, escalating to 89% by cycle II. The study concludes that integrating the PjBL model in PJOK subjects significantly fosters students' healthy living behaviors, demonstrating that active, project-based approaches can effectively instill essential health practices from an early age.